2016
DOI: 10.1038/am.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Coating sponge with a hydrophobic porous coordination polymer containing a low-energy CF3-decorated surface for continuous pumping recovery of an oil spill from water

Abstract: For the remediation of oil spills and organic solvent leakage into water, it is desirable to develop not only advanced sorbents with a high adsorption capability but also labor-and time-saving apparatuses that can work continuously without human intervention. In this work, we synthesized a novel and highly stable porous coordination polymer (PCP, also called metal-organic framework), University of Science and Technology of China-6 (USTC-6), with a corrugated -CF 3 surface that features high hydrophobicity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 54 publications
(62 reference statements)
1
77
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28] A great effort has been dedicated to fabricating porous materials with hierarchical porosity with a large specific surface area and being water resistant. Stable hydrophobic MOFs were prepared using hydrophobic functional (F and alkyl) organic linkers or through postsynthetic modification of MOF using hydrophobic groups; although, one cannot rely on many typical MOFs for the oil adsorption due to their microchannels.…”
mentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] A great effort has been dedicated to fabricating porous materials with hierarchical porosity with a large specific surface area and being water resistant. Stable hydrophobic MOFs were prepared using hydrophobic functional (F and alkyl) organic linkers or through postsynthetic modification of MOF using hydrophobic groups; although, one cannot rely on many typical MOFs for the oil adsorption due to their microchannels.…”
mentioning
confidence: 99%
“…Sorbents are materials with high affinity to oils and a little to water, which due to two simultaneously occurring processes: adsorption (involving the oil adhesion to the surface of the sorbent, the extent of which depends on the viscosity of the oil) and absorption (consisting in filling the pores of the material by oil, which can be taken out of the water along with the sorbent due to the capillary force) allow for the removal of toxic oil substances from water in a non-invasive manner [9]. Among the most important material properties affecting the efficiency of oil removal from water, a high absorption capacity is mentioned in relation to the most of the oily substances [10][11][12][13][14][15][16][17]. The experiment demonstrated that the most effective materials in lowering the n-alkanes concentrations within the range of C7H16-C38H78 (these alkanes compose the oil contamination [2]) include birch bark and glass wool.…”
Section: Resultsmentioning
confidence: 99%
“…One such method is based on sorption, i.e. the physical method of de-oiling, during which two processes occur simultaneously: absorption of oil within the pores and voids of sorbent as well as oil adsorption on its surface [6,15]. Among sorbents, materials of a porous nature are the most commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated the presence of an adsorption competition between water and toluene in the adsorbents. Many studies have also shown the great potential of hydrophobic MOFs or their derived materials for bulk oil/water separation and bulk oil adsorption from water for the cleanup of oil spills . The removal of other types of harmful or useful gases or organic substances, such as ethylene, acetic acid, thiophene, peptides, aromatic amino acids, and pharmaceuticals, from air or water by hydrophobic MOFs and their derived materials has also been documented.…”
Section: Potential Applicationsmentioning
confidence: 99%